Mixed Allyl Rare‐Earth Borohydride Complexes: Synthesis, Structure, and Application in (Co‐)Polymerization Catalysis of Cyclic Esters. Issue 62 (16th October 2017) - Fadlallah, Sami; Jothieswaran, Jashvini; Capet, Frédéric; Bonnet, Fanny; Visseaux, Marc
Abstract: A series of new trivalent rare‐earth allyl–borohydride complexes with the formula [RE(BH4 )2 (C3 H5 )(thf) x ] (RE=Sc (1 ), x =2; RE=Y (2 ) and La (3 ), x =3) were synthesized by reaction of the corresponding rare‐earth trisborohydrides [RE(BH4 )3 (thf) x ] with half an equivalent of bis(allyl)magnesium. The complexes were fully characterized by determining their X‐ray structure. Similar to their previously described Nd (4 ) and Sm (5 ) analogues, these complexes display a monomeric structure with two terminal trihapto BH4 groups, one π–η 3 allyl ligand, three THF molecules for complexes2 and3, and two THF molecules for complex1 . The catalytic behavior of complexes1 –5 toward the ring‐opening polymerization (ROP) ofl ‐lactide (l ‐LA) and ϵ‐caprolactone (ϵ‐CL) was assessed. The Nd complex featured the best activity towardl ‐LA (turnover frequency (TOF)=1300 h −1 ) and the order was Nd>La>Sm>Y>Sc. Complexes1 –3 were found very active for the ROP of ϵ‐CL (TOF=166 000 h −1 ), which is in line with the already established exceptionnally high performance of complexes4 and5 . With both monomers, it was shown that the borohydride moiety was the preferentially initiating group, rather than the allyl one. The random copolymerization ofl ‐LA and ϵ‐CL was performed with complexes1 –5, in the absence or in the presence of benzyl alcohol as a chain‐transfer agent, affording copolymers with ϵ‐caprolactone up to 62 % inserted. The copolymers synthesized display a variety of microstructures, that is, blocky, random, or quasi‐alternating. Abstract : A rare find : A series of new synthesized rare‐earths (RE) complexes bearing borohydrido and allyl moieties was investigated with regard to their ability of catalyzing the ring‐opening polymerization ofl ‐lactide (l ‐LA) and ϵ‐caprolactone (ϵ‐CL) (see figure) and of mixtures of both monomers, giving rise tol ‐LA–ϵ‐CL copolymers with different compositions.